Supporting Open Access to Teaching and Learning of People with Disabilities - Zervas, P.; Kardaras, V.; Baldiris, S.; Bacca, J.; Avila, C.; Politis, Y.; Deveril; Treviranus, J.; Fabregat, R.; Goodman, L.; Sampson, Demetrios (2014)
Over the past years, several frameworks have been developed aiming to support inclusive learning by the provision of flexible or individualized learning experiences. These frameworks recognize the broad diversity of learners and they provide specific learning design principles to ensure accessibility of all learner types to the learning environment or education delivery. In the field of technology-enhanced learning (TeL), accessibility has been recognized as a key design consideration for TeL systems, ensuring that learners with diverse needs and preferences (such as learners with disabilities) can access technology-supported resources, services, and experiences, in general. Within this context, several initiatives have emerged, such as the Inclusive Learning project, which aims to promote an inclusive learning culture and support teachers in designing, sharing and delivering accessible educational resources in the form of learning objects (LOs). To this end, the scope of this book chapter is to present an online educational portal, namely the Inclusive Learning Portal, which aims to support open access to teaching and learning of people with disabilities. More specifically, the Inclusive Learning Portal architecture is presented, which contains a repository of accessible LOs, complementary services that enable easy development and delivery of accessible LOs, as well as teacher training opportunities in the use of these services.